#33 Formulation and evaluation of Dexketoprofen proniosomal gel - Bhargava, Tanu; Dashora, Kamlesh (Journal of Pharmaceutical Chemistry, 2022)
Current research is based on the development and differentiation of transdermal proniosome-based gel. The modified proniosomal gel shows good stability, release, following zero-order kinetics, maximum zeta power is ±49 mV. The pH of the whole composition was close to the skin pH 7.11 to 7.20 the drug content in the formulation was within an estimated range of 92-97%. The composition of the gel can be sorted as follows with regard to the viscosity of the drug: Dt3 > Dt2 > Dt9 > Dt7 > Dt4 > Market gel > Dt6 > Dt5 > Dt1 > Dt8. Span 40 & span 60 (50:50) proniosomal gel showed a drug release up to 12 h. The encapsulation efficiency of proniosomal gel formation ranges from 82.10% to 94.12%. Analysis of the proniosome-based niosome particle size shows that the SD (nm) particle size is 209.5 nm with a polydispersity index of 0.182.
Keywords: aaa